Rheological properties of bitumen modified with a combination of FT paraffin wax (Sasobit®) and other additives - Fazaeli, Hassan; Amini, Amir A.; Moghadas Nejad, Fereidoon; Behbahani, Hamid (Journal of Civil Engineering and Management, 2016)
Fischer–Tropsch paraffin Sasobit® is a popular Warm Mix Asphalt (WMA) modifier applied to improve physical and rheological properties of bitumen. Although there are a number of studies investigating the effects of sasobit on bitumen properties, little has been carried out on evaluation of bitumen modified by sasobit along with other additives. In this study, sasobit modified bitumen is used as the base condition and four common modifiers namely anti-stripping agent, Crumb Rubber (CR), Styrene–Butadiene–Styrene (SBS) and Polyphosphoric Acid (PPA) are added separately to the FT – Wax modified bitumen to evaluate the compatibility of these additives with sasobit. Morphological, rheological and physical properties of modified binders are studied using Fourier Transform Infrared Spectroscopy (FT-IR), Scanning Electron Microscopy (SEM), Dynamic Mechanical Analysis (DMA), Bending Beam Rheometer (BBR) alongside with conventional tests. Results show that although anti-stripping agent reduce bitumen viscosity and mixing/compaction temperatures of asphalt mixtures, it has significantly increased the stiffness of sasobit modified bitumen at low temperatures. Among all, sasobit and crumb rubber combination exhibited the best performance, especially at low and intermediate temperatures.